OPTIMIZATION OF THE PREVENTION OF ANOMALIES OF OCCLUSION OF THE DENTITION IN THE PERIOD OF TEMPORARY OCCLUSION - Mukhammed Erkinov Akramovich; Begzod Tursunov Sherzodovich; Akmal Roziev Akramovich (Scholar Express Journals, 2023)
This article discusses in detail the optimization of the prevention of malocclusion during the period of temporary occlusion, the author's postoperative therapeutic protocol, which is very important for determining the final and permanent preservation of the corrected occlusion.
Keywords: occlusion; therapeutic protocol; surgical fixation; rigid fixation